أسـاليب القـرآن الكـريم ومميـزاتهـا (دراسـة مقـارنـة أدبيّـة( - M. Rasyid Ridha (State Institute of Islamic Studies (IAIN) Palu, 2008)
In the period of Jâhiliyyah, the Arabs always felt proud of their language. They also competed with each other for selecting a particular literary style in expressing their words and beautifying dictions in their poetry and prose. However, when Alquran was revealed, they did not find such literary style as the Qur’an’s. They chose words as refined and perfect as the Qur’an’s. This is one of the driving reasons to study and compare the Qur’an’s literary style and one which has been used so far in Arabic expressions. One of the factors might be that the Qur’an’s literary style covers myriad of meanings.Kata Kunci: Alquran, uslub bahasa Arab